Status 25(OH)D pada Penderita Sindrom Metabolik, Komponen Sindrom Metabolik, dan Orang Dewasa Sehat: 25(OH)D Status in Metabolic Syndrome, Metabolic Syndrome Components, and Healthy Adult - Efriwati, Efriwati; Ernawati, Fitrah; Nurjanah, Nunung; Julianti, Elisa Diana; Aji, Galih Kusuma; Sundari, Dian; Retiaty, Fifi; Arifin, Aya Yuriestia (Universitas Airlangga, 2024)
Background: Vitamin D supplementation to prevent Metabolic Syndrome (MetS) has been widely implemented in developed countries and is now being introduced in developing countries. However, recent studies have shown no association between vitamin D and MetS in adults. Objectives: This study aims to obtain a profile of vitamin D values ​​in adults and explore vitamin D status in MetS patients, MetS components, and healthy adults. Methods: This research design was a cross-sectional study, utilizing both secondary and primary data from the research on the Risk Factors for Non-Communicable Diseases (RF-NCD) longitudinal study in 2021. Serum 25(OH)D levels in 956 adult respondents were determined by Enzyme-linked Immune Assay (ELISA) analysis using Stored Biological Material (SBM) serum from the 2021 RF-NCD longitudinal study. The ANOVA test was used to determine differences in vitamin D levels in various physiological conditions of respondents (MetS, MetS components, and healthy people). Results: A total of 68.5% of respondents had inadequate (deficiency and insufficiency) serum vitamin D levels, with an average of 26.5 ng/mL. The average vitamin D levels between MetS patients, MetS components, and healthy people were not significantly different (p-value>0.05). However, the number or percentage of respondents with 25(OH)D deficiency in the MetS group (12.1%) was higher than other physiological conditions. Conclusions: Most of the respondents in this study have inadequate vitamin D levels. The average vitamin D levels did not differ between physiological conditions. Further studies are needed on other micronutrient factors that affect the incidence of MetS and its components.